E-INTEGRATIVE CONTROL SYSTEM AS A COMMUNITY ORGANIZATION SUPERVISION DESIGN TO REALIZE THE CONCEPT OF STATE - Wahyu Beny Mukti Setyawan; Fery Dona (Jurnal Hukum, 2020)
The government, as the party that has the mandate from the people tosa feguar ditsso vereignty, has revoked permits for the establish men to social organizations which are deemed contrary to the ideology of the State. The Ministryof Law and Human Rights as the party that grants the permit can immediately revokethelicense on the basis of the contractus actus principleÂ  contained in the Perppu No. 2 of 2017 concerning Amendmentsto Law No. 17 of 2013 concerning Community Organization. Even though they have taken repressive steps, the Ministry of Law and Human Rights has not taken any preventiveaction in obstructing and preventing theemergence of social organizations that are contrary to the ideology of the State. There fore the authors providean effective solution in theformofan E-Integrative Control System as a Social Organization Supervision Design to Realize the Concept of State Sovereignty so that the Government as the party responsible for granting perm its for the establish men to social organizations and contradicting stateideology. Which could threaten theso vereigntyandintegrity of the Unitary State of the Republic of Indonesia.